Olfactory Characterization and Training in Older Adults: Protocol Study - Zambom-Ferraresi, Fabíola; Zambom-Ferraresi, Fabricio; Fernández-Irigoyen, Joaquín; Lachén-Montes, Mercedes; Cartas-Cejudo, Paz; Lasarte, Juan José; Casares, Noelia; Fernández, Secundino; Cedeño-Veloz, Bernardo Abel; Maraví-Aznar, Enrique; Uzcanga-Lacabe, Maria Itziar; Galbete, Arkaitz; et al. (Frontiers in Aging Neuroscience, 2021)
The aim of this article is to present the research protocol for a prospective cohort study that will assess the olfactory function and the effect of an intervention based on olfactory training in healthy very old adults (≥75 years old). A convenience sample of 180 older people (50% female) will be recruited in three different environments: hospitalized control group (CH) with stable acute illness (n = 60); ambulatory control group (CA) of community-based living (n = 60); and an experimental odor training group (EOT) from nursing homes (n = 60). The odor training (OT) intervention will last 12 weeks. All the volunteers will be assessed at baseline; CA and EOT groups will also be assessed after 12 weeks. The primary end point will be change in olfactory capacity from baseline to 12 weeks period of intervention or control. The intervention effects will be assessed with the overall score achieved in Sniffin Sticks Test (SST) – Threshold, Discrimination, and Identification (TDI) extended version. Secondary end points will be changes in cognitive tasks, quality of life, mood, immune status, and functional capacity. All these measurements will be complemented with an immune fitness characterization and a deep proteome profiling of the olfactory epithelium (OE) cultured ex vivo. The current study will provide additional evidence to support the implementation of olfactory precision medicine and the development of immunomodulatory nasal therapies based on non-invasive procedures. The proposed intervention will also intend to increase the knowledge about the olfactory function in very elderly people, improve function and quality of life, and promote the recovery of the health.